Validation of the Greek version of the Family Problem Solving Communication Scale (FPSC) in breast cancer patients - Dimitrios Charos; Maria Andriopoulou; Giannoula Kyrkou; Anna Deltsidou; Nikolas Amplas; Maria Kolliopoulou; Grigorios Karampas; Victoria Vivilaki (Cogent Psychology)
Family plays a vital role in supporting breast cancer patients. Recent studies have shown that increasing family resilience empowers family support for patients. The study aims to validate the Family Problem Solving Communication (FPSC) scale in breast cancer patients in the Greek population. A factor analysis was performed, and convergent validity and reliability were tested through Cronbach alpha, Split-Half reliability, Spearman-Brown Coefficient, and Guttman Split-Half Coefficient. According to the factor analysis, Bartlett’s Test of Sphericity coefficient (Chi-Square = 439.105, p = 0.000) showed that it has statistically significant correlations between items and the KMO index was 0. 860. The Cronbach α coefficient was 0.78, the Spearman-Brown coefficient was 0.603 and the Guttman Split-Half coefficient was 0.596. Finally, there was a correlation of the scale with FAD (r=0.328, F-COPES (r=0.290), and ECR-R (r=–0.424). The FPSC scale demonstrates satisfactory psychometric properties and is a suitable and useful psychometric instrument for investigating family resilience.